CONCERNS ON USING COAL SPOIL DUMPS (COLLIERY SPOILS) AS SUB-STANDARD MATERIALS FOR CONSTRUCTION MATERIALS - M. Eddie Sunaryo (Jurnal Jalan-Jembatan, 2007)
The developing infrastructure sectors are increased as a result that there have been increasingly demands for the use of Standard Materials and influenced the increasing construction costs and has been predicted to increase still future. The use of Sub-standard Materials to replace the Occurrence of Standard Materials is now being strongly recommended as a solution however there is Any Test Guides do not deal appropriate to them due to indicate the different results due to an experiencing behaviour of the actual field performance. The use of sub-standard materials are being encouraged due to the regulation on maintaining the environmental balance, so therefore, the use of suitable standard materials have been limited. Further, the uses of sub-standard materials (local materials) have been also urged by the government body or any country, who are aware and responsible to the damages or changes of the environmental balance caused by land contaminations however may commonly susceptible to changes on their characteristic either in chemically or physically as a result of reacting processes when they contact with other mineral substances, such as water and air. The ‘unburnt spoils’ (minestone) as sub-standard materials are most found rather ‘burnt spoils’ and can be used as material contractions such as ‘fill materials’, ‘road base’ and ‘sub-base’ of materials in road constructions after the following recommendations, such as removing or protecting and treating the spoil dump heap to prevent the ground water pollutions, upgrading using thermal treatment towards basic materials for producing the quality of construction materials, investigating the occurrences of the potential leachability and economic calculations to get a brief overview of the Costs of Mineral Product (COMP) when used as material constructions. Keywords : Sub - standard materials, Industrial and man-made by product, Coal spoil disposals, Material constructions, Utilizing solution.